Essays in honour of Michael Bliss : figuring the social - Li, Alison, 1963-; Heaman, E. A. (Elsbeth A.), 1964-; McKellar, Shelley; Bliss, Michael (University of Toronto Press, 2008)
A leading public intellectual, Michael Bliss has written prolifically for academic and popular audiences and taught at the University of Toronto from 1968 to 2006. Among his publications are a comprehensive history of the discovery of insulin, and major biographies of Frederick Banting, William Osler, and Harvey Cushing. The essays in this volume, each written by former doctoral students of Bliss, with a foreword by John Fraser and Elizabeth McCallum, do honour to his influence, and, at the same time, reflect upon the writing of history in Canada at the end of the twentieth century.The opening essays discuss Bliss's career, his impact on the study of history, and his academic record. Bliss himself contributes an autobiographical essay that strengthens our understanding of the business of scholarship, teaching, and writing. In the second section, the contributors interrogate public mythmaking in the relationship between politics and business in eighteenth-, nineteenth-, and twentieth-century Canada. Further sections investigate the relationship between fatherhood, religion, and historiography, as well as topics in health and public policy. A final section on 'Medical Science and Practice' deals with subjects ranging from early endocrinology, lobotomy, the mechanical heart, and medical biography as a genre. Going beyond a collection of dedicatory essays, this volume explores the wider subject of writing social and medical history in Canada in the late twentieth century.